Acacia koa seedling disease tolerance and vigor driven by breeding orchard size - Fumia, Nathan; Dudley, Nicklos; Jones, Tyler; Dobbs, John; Stewart, Jane; Kantar, Michael (Frontiers in Plant Science, 2025)
Acacia koa Gray (koa) is a Hawaiian endemic tree species that has a long history of use in the islands. In the late 20th century disease started impacting native koa stands, leading to the initiation of seed orchards that were founded from seeds collected across the islands. Large improvements in disease tolerance and vigor were achieved in very few cycles of selection despite the long temporal time of this perennial hardwood tree species. Initial selection on agronomic and domestication traits improved populations to the agricultural and natural ecosystem. Further, using simulation we identified how different methods of selection could be implemented to more rapidly make progress toward improved koa germplasm. Our evidence shows that domestication in Acacia koa provides a model for parametrization of crossing in the breeding cycle for rapid improvement of any tree species.